Comparison of Second-Trimester Uterine Artery Doppler Indices between Pregnant Women with and without Prior Cesarean Delivery and Effect on Perinatal Outcomes - Bundaree Chaiprasit; Suthasinee Mataneedol; Buppa Smanchat; Kornkarn Bhamarapravatana; Komsun Suwannarurk (Siriraj Medical Journal)
Objective: To evaluate the effects of prior cesarean delivery on second-trimester Uterine Artery (UtA) Doppler and its effect on perinatal outcomes.